Stratified saturated control of bacteria migration in porous media: an experimental investigation (2013)
"The importance of sand bed filters has gained more ground in on- site water treatment facilities. The performance of which depends on the design of the sand bed. A laboratory column experiment was designed to quantitatively determine the best kind of sand layered arrangement for maximal bacteria attenuation. Porosity was taken as media parameter to further examine the relationship between the layers that will yield a better performance. Porosity was determined using volumetric approach and vertical downward flow for the column filtration. Escherichia coli and Staphylococcus aureus was used as contaminants. The results revealed that the larger the difference in porosity of the layers the better the filter performance and that least porous material should be below followed by the larger one arranged in the direction of flow. It was also shown that for homogeneous layered media, the more the number of layers, the better is the filter performance. These inferences would help in better design of stratified sand filter systems both for water purification and fishpond effluents treatment systems."